Gambaran Kepatuhan Minum Obat Antituberkulosis Pasien Tuberkulosis Paru di Wilayah Kerja Puskesmas Pekanbaru Kota - Neni Ristiani; Ahmad Mutta’in; Endang Widi Astuti; Melinia Cahaya Fitri; Serli Alnamira Lorenza; Uly Santika Wulan (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Patient adherence to tuberculosis (TB) treatment is crucial for achieving a cure, preventing transmission, and avoiding cases of drug resistance. TB treatment typically involves using antibiotics for 6-9 months. Consistent compliance during this period is essential to ensure the eradication of the bacteria that cause TB. Non-compliance can result in disease recurrence and the development of drug resistance. Many factors can influence patient compliance, including drug side effects, lack of social support, patient knowledge about the disease, economic factors, and accessibility of health services. This study aims to provide an overview of the level of patient compliance in tuberculosis treatment at the Pekanbaru City Health Center. This research is a descriptive study with a cross-sectional method conducted on 37 respondents using a survey method via questionnaire. The result of the research found that 54.1% of respondents at the Pekanbaru City Health Center had a moderate level of compliance with TB treatment.